2015
DOI: 10.1128/jvi.03693-14
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties and Genetic Relatedness of the Fusion and Hemagglutinin-Neuraminidase Proteins of a Mumps Virus-Like Bat Virus

Abstract: A bat virus with high phylogenetic relatedness to human mumps virus (MuV) was identified recently at the nucleic acid level. We analyzed the functional activities of the hemagglutinin-neuraminidase (HN) and the fusion (F) proteins of the bat virus (batMuV) and compared them to the respective proteins of a human isolate. Transfected cells expressing the F and HN proteins of batMuV were recognized by antibodies directed against these proteins of human MuV, indicating that both viruses are serologically related. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Expression plasmids encoding for the envelope glycoproteins of EBOV, BDBV, TAFV, RESTV, SUDV, MARV, LLOV, NiV, MuV, LASV, LCMV, MACV and VSV have been described previously (Hoffmann et al, 2016;Wrensch et al, 2014;Krüger et al, 2015). The plasmids required for the trVLP system (Watt et al, 2014) and VP30-luciferase containing particles have also been described before (Hoffmann et al, 2017).…”
Section: Plasmidsmentioning
confidence: 99%
“…Expression plasmids encoding for the envelope glycoproteins of EBOV, BDBV, TAFV, RESTV, SUDV, MARV, LLOV, NiV, MuV, LASV, LCMV, MACV and VSV have been described previously (Hoffmann et al, 2016;Wrensch et al, 2014;Krüger et al, 2015). The plasmids required for the trVLP system (Watt et al, 2014) and VP30-luciferase containing particles have also been described before (Hoffmann et al, 2017).…”
Section: Plasmidsmentioning
confidence: 99%
“…We inoculated cell lines from different host species, including those standardly used for FLUAV research, as well as cell lines derived from different bat species (Table 1), as they are the natural reservoir for batFLUAV. We chose bat cell lines known to be susceptible to infection by viruses of different families [28,29,31] and previously used to functionally characterize surface glycoproteins of bat-borne viruses [28,36,38]. It is well established that FLUAV-HA depends on proteolytic cleavage by host cell proteases to transit into an active form [12] and it has been previously reported that batFLUAV can be activated by exogenous trypsin [39][40][41].…”
Section: Hal Of Batfluav Mediates Cellular Entry Into Bat Cell Lines mentioning
confidence: 99%
“…Viral RNA of batMuV, a virus closely related to hMuVs, has been detected in an African fruit bat, but no infectious virus has been isolated. To date, studies of batMuV have been limited to either expression of individual batMuV proteins in cell cultures (Kr€ uger et al, 2015) or generation of recombinant chimeric hMuVs modified to encode the batMuV glycoprotein genes (Katoh et al, 2016;Kr€ uger et al, 2016;Beaty et al, 2017). However, in the absence of the use of authentic batMuV, the significance of these observations remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were fixed with 4% paraformaldehyde and permeabilized with 0.2% Triton X-100. Viral proteins were detected by incubation with antibodies directed against MuV N (N 5495, mouse), P (P 2037, mouse), M (M 2124, mouse) (Ö rvell, 1984), the cytoplasmic tail of MuV F (rabbit) (Kr€ uger et al, 2015), the ectodomain of MuV HN (rabbit) (Ö rvell, 1978) or neutralizing antibodies against MuV Kilham strain (rabbit) (Ö rvell et al, 1997) in a humidity chamber for 1 h. HA-labeled V, I and SH proteins were detected by incubation with antibodies directed against the HA epitope (mouse, Sigma-Aldrich). Cellular NF-kB p65 was detected by incubation with polyclonal NF-kB p65 antibodies (rabbit, Thermo Fisher Scientific).…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%